Children of drug addicts: their perceptions on intra-family relationships - Rey, Diana Machado (2020)
The perception of children of drug-dependent parents on family functioning and affectionate relationships with their parents is described. Current qualitative study has been conducted with four children, children of drug addicts. Data were collected through family genogram and semi-structured interview. The statements were submitted to content analysis. Family functioning was classified as careless, entangled in border strengthening, or non- classified. Attachment types were safe and preventive. Family functioning is related to the forms of interaction between members and not to the use of psychoactive substances. Dependency is not the triggering factor of the system´s rigidity, but a consequence of the predominant style of attachment. It hinders positive interactions and the search for alternative patterns of functioning, being an important risk factor for healthy development of its members.